Understanding the Factors Influencing the Participation of the Warehouse Receipt System Program for Pepper Farmers. - R Ferry Bakti Atmaja; Yosefin (Conference Series, 2020)
The Warehouse Receipt System is a government program aimed at improving the welfare of small farmers, enabling them to postpone the sale of their goods to be stored in government warehouses and sold at a more profitable price. In practice, it shows the low level of farmer participation. This research is a qualitative study, trying to describe the causes of the problem through door-to-door interviews and questionnaires to pepper farmers. The results showed that several reasons that influenced and prevented pepper farmers from participating in the WRS program included the amount of pepper production produced by small-scale farmers, the lack of confidence of farmers in the program due to the absence of a pilot program, storage costs in warehouses were considered burdensome, farmers' reluctance to deal with bank loans due to complicated procedures and emotional feelings of local residents.